The Influence of Squat Jump Training on Leg Muscle Power of Pesilat at Education of Pencak Silat Persinas Asad Bangkalan - Tiazari Cindiantika Fitri; Heni Yuli Handayani; Fajar Hidayatullah; Fajar Hamdhan Utama (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to describe the implications and responses of fighters on the use of Squat Jump exercises in learning pencak silat. The research design in this study is quantitative. This research involved martial arts fighters aged 14-17 years at the Persinas Asad Pencak Silat College as research subjects. The data were obtained through martial arts, in this study the researcher carried out several stages to analyze the data, namely the pre-test and post-test. The results of the study show that the use of squat jump exercises is effective in the process of practising pencak silat because fighters get something different by using squat jump exercises. The squat jump exercise is also used to provide input to fighters to get good leg muscle power. According to fighters, squat jump training is a training model that invites fighters to further increase leg muscle power. In addition, fighters can also provide more power when kicking pencak silat.